Treatment outlines for non-complicated Carrion´s Disease, in Caraz, Peru - Arroyo, Álvaro (2008)
Objectives: To describe Bartonella bacilliformis’ infection treatment, in Caraz, Ancash. Design: Observational, transverse and retrospective study. Setting: Caraz, Ancash, Peru. Patients: Five hundred and eighteen patients. Interventions: Study of clinical histories data from January 2004 through March 2005 at Caraz Hospital. Main outcome measures: Treatment outlines for Bartonella bacilliformis infection. Results: In the acute phase, 248 patients were registered; in 215 (86,7%) chloramphenicol treatment was indicated but the 50 mg/kg loading dose by 3 days was not prescribed; 164 (66,1%) patients needed a higher chloramphenicol dose of 25 mg/kg. In the eruptive phase, 270 patients were registered; in 260 (96,3%) rifampicin was indicated and 222 (82,2%) for more than the 21 treatment days suggested for this antibiotic. Clinical cure was obtained with chloramphenicol in 89% and 93,1% with rifampicin. Conclusions: In the population studied there was a tendency to increase both chloramphenicol dose and rifampicin number of treatment days respectively in the acute and eruptive phases of Carrion’s disease.